Retinopathy of PrematurityPrevalence and High Risk Characteristics in a Rural Tertiary Care Hospital in Central India - Bodhraj Dhawan; Rekha Khandelwal; Kanav Gupta (JCDR Research and Publications Pvt. Ltd., 2016)
Introduction: Retinopathy of Prematurity (ROP), a disease characterized formation of a vascular barrier at junction of vascularized and non-vascularised retina is increasingly being common in developing countries due to increasingly improving neonatal fascilities. Various factors have been implicated in its causeation. Aim: Present study aimed to find prevalence of ROP and associated risk factors in rural tertiary care hospital setting. Materials and Methods: During study period, ROP screening and treatment was done by a trained retina specialist for neonates at 4-6 weeks after birth or at 31 weeks post menstrual age, whichever is later, using dilated indirect ophthalmoscopy with a 28 Dioptres condensing lens in Neonatal ICU. Risk factors including gestational age, birth weight and neonatal risk factors were noted and ROP, if present was classified and noted. Eligible babies were offered treatment. Results: Prospective study to screen 50 premature babies was undertaken over the study period of 18 months in which 11 babies (22%) were found to have ROP. The birth weight of ROP babies ranged from 968- 1650 grams with a mean weight of 1260.90 ± 215.52 gm, while that of non-ROP babies ranged from 900-2900 gm, with a mean weight of 1517.07 ± 419.04 grams. Similarly, the gestational age of ROP babies ranged from 28-36 weeks with a mean gestational age of 30.54 ± 2.54 weeks; while that of non-ROP babies ranged from 28- 39 weeks with a mean age of 33.12 ± 3.05 weeks. The difference of mean weights between two groups was statistically significant with p-value of 0.0097 (p< 0.05). Also the difference of mean gestational age between two groups was significant with p-value of 0.0105 (p< 0.05). Low birth weight and low gestational age were identified as main significant risk factors.Apnoe, oxygen administration and respiratory distress were other risk factors noted. Conclusion: ROP is a common issue in premature and low birth weight babies. ROP Screening should therefore be followed as standard protocol in paediatric NICU settings.